Building Design for Lateral Earthquake Forces on a Multi-Story Reinforced Cement Concrete (RCC) Structure Including a Shear Wall - Islam Mahidul; Arafat Easin; Meer Shafiul Azam (Journal of ICT, Design, Engineering and Technological Science, 2023)
The primary goal of this research was to determine how modifying the Shear Walls may improve the design of a multi-story skyscraper. Under static and dynamic load, four possible shear wall orientations for a 25-story skyscraper have been studied in line with BNBC 1993 rules using the analytical programme ETABS. Forces on columns and beams are seen to grow on the grid in the direction opposite to the movement of the Shear Wall from the building's centre of mass. Members' twisting moments are found to increase when the eccentricity between the geometric centre of the structure and the position of the shear wall is larger. Elements of the Shear Wall that are perpendicular to the displacement direction of the Shear Wall are less affected by the stress than those that are parallel to it. The building's lateral movement is constant in a zero-eccentricity example. However, if the Shear Wall is positioned erratically, the drift will be more pronounced on one side of the grid than the others. It is determined that the optimal location for the shear wall is where the building's centre of mass and centroid meet. Also this study Insights into eccentricity and its effect on lateral drift provided by the study offer recommendations for mitigating building sway and vibrations. By broadening the scope of the investigation to encompass the distinct consequences of seismic forces on various shear wall orientations, the signi